A deadly bone to pick - Rothschild, Peggy ([A Molly Madison mystery, 2022)
"When Molly Madison, dog-wrangler extraordinaire, stumbles upon a murder in her new hometown, she must track down a killer to save the day. Ex-police officer and former private investigator Molly Madison is starting over. After the death of her husband, she and her golden retriever, Harlow, move cross-country to California. But as charming and peaceful as the beachside town seems, she soon learns its tranquil tides hold dark secrets. On her first day in the new house, a large, slobbering Saint Berdoodle wanders in. Molly winds up taking on the responsibility of training Noodle since his owner is too busy to do the job. During one of their daily beachside walks, Noodle digs up a severed hand. Once Molly alerts the police and they run a background check on her, an incident from her past makes her an immediate suspect-after all, Noodle's testimony to clear her name won't hold much water in court. To prove her innocence, Molly must rely on instincts keener than a canine's to sniff out the real killer. But when Molly's life is put in danger, will her two very loyal pups be able to rescue her?"--